The Urban Metabolism of the City of Uppsala (Sweden) - Russo, Tommaso; Buonocore, Elvira; Franzese, Pier Paolo (Journal of Environmental Accounting and Management, 2026)
Urban systems can be considered like living organisms supplied by mate- rial and energy flows used to maintain structures an functions, and the production of goods and services. In this paper, we integrate economic cost analysis with a method of biophysical accounting (namely Emergy Synthesis) to assess the main inputs and output flows characterizing the urban metabolism of the city of Uppsala (Sweden). Natural and human- driven resource flows supporting the metabolism of the city were evalu- ated and compared by using an ecological-economics perspective. Final- ly, economic and emergy-based indicators were calculated and discussed. Results highlighted a lack of self-sufficiency characterizing most of mod- ern cities especially in terms of food andenergy supplied from larger environmental systems. Considering the existing problems of environ- mental sustainability of most cities and the current trend towards urbani- zation, the proposed multi-criteria assessment to the study of urban me- tabolism, further improved by a deeper investigation of social variables, can represent an important component of sustainability research and poli-Cy.